Hormonal Control of Adrenocortical Cell Proliferation: DESENSITIZATION TO ACTH AND INTERACTION BETWEEN ACTH AND FIBROBLAST GROWTH FACTOR IN BOVINE ADRENOCORTICAL CELL CULTURES - Hornsby, Peter J. (1977)
A primary bovine adrenocortical cell culture system responsive to physiological concentrations of ACTH has been established. When added to cultures, ACTH inhibited DNA synthesis and cell division over the same concentration range required for stimulation of fluorogenic steroid production (0.01-10 nM). With chronic exposure to ACTH, cells became desensitized to the growth inhibitory effects of ACTH. Though cell growth was initially completely inhibited by ACTH, cells ultimately began to grow in its continued presence. The lag time to initiation of cell growth, the rate of growth, and the final density achieved depended on the ACTH concentration. Desensitization to ACTH(1-39) was not induced by monobutyryl cyclic AMP nor by ACTH(11-24). Specificity of desensitization was apparent because cells which had become desensitized to ACTH(1-39) remained fully responsive to monobutyryl cyclic AMP, prostaglandin E(1), and cholera toxin. Though the effects of ACTH on cell growth were readily reversible upon hormone removal, the desensitized response to readdition of ACTH persisted for at least 8 h. Fibroblast growth factor (FGF) stimulated both the growth rate and saturation density achieved. FGF did not alter the growth inhibitory effects of ACTH nor the reduced growth rate observed in desensitized cells maintained in ACTH. However, FGF greatly increased the saturation density achieved by cultures maintained with ACTH. Through the process of desensitization, adrenocortical cells are able to grow in the presence of high concentrations of ACTH and to respond to the effects of a growth factor by increasing the cell density achieved. This pattern of response may be a general one for growth control under the combined effects of antimitotic and mitotic factors.